REVOLUTIONIZING CULINARY BUSINESS: HOW ONLINE FOOD DELIVERY, FINTECH, AND DIGITAL MARKETING DRIVE INCOME GROWTH FOR SMES - Tantri, Anita Lia; Sariwulan, Rd. Tuty; Nikensari, Sri Indah (Faculty of Economics and Business, Universitas Negeri Jakarta, 2024)
The main objective of this study is to examine the impact of online food delivery, financial technology, and digital marketing on the revenue of Micro and Small Enterprises (MSEs) culinary sector, using a quantitative methodology. This study involved a sample of 100 MSEs in Bekasi City that have integrated online food delivery services, financial technology solutions, and digital marketing strategies into their operational framework. Data analysis includes, instrument validity and reliability tests, normality tests, linearity tests, classical assumption assessments, multiple linear regression analysis, and hypothesis testing through partial analysis (t-test). The findings of this study indicate: (1) Online food delivery services have a significant impact on business revenue; (2) The use of financial technology has a significant impact on business revenue; and (3) The implementation of digital marketing strategies has a significant impact on business revenue. The results of this study underline the important roles played by online food delivery, financial technology, and digital marketing in improving the revenue generation capacity of MSEs in the culinary sector.